"ФАУСТ" АСАРИ ТУРЛИ ТАРЖИМАЛАРИ ҚИЁСИЙ ТАҲЛИЛИ - Назаров, С.Х. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of translation of the work «Faust» by I.V.Goethe into Turkish. It deals with the history of «Faust» and the issues of using and recreating of expressive means in translation. The author analyses the research works and recommendations of the Uzbek and foreign scholars to the book «Faust». The study of literary translation taking into account the time and place is very important. The conception of personality in different religions, mentalities and views is shown in the image of Faust.
Keywords: translation; image; dramatic; tragedy; direct; indirect; style; allegory; epithet